Effect of Dietary Protein Deficiency on the Activity of Cytochrome P450 Enzyme Systems in the Liver of Rats of Reproductive Age Under Acetaminophen-Induced Injury - Nykolaichuk, Ivanna; Kopylchuk, Нalyna (My University, 2022)
In this study, we aimed to evaluate the effect of dietary protein deficiency on the activity of cytochrome P450 enzyme systems - p-hydroxylation, N-demethylation, N-oxidation in the liver of rats of reproductive age under acetaminophen-induced injury. Within this topic, we investigated the content of cytochrome P450 and the rate of its inactivation in the inactive form of P420, as well as the intensity of generation of superoxide anion radical under experimental conditions. During the experiment, the experimental animals consumed a semi-synthetic diet AIN-93 in accordance with the recommendations of the American Institute of Nutrition. In order to model the alimentary protein deprivation rats received a low-protein diet daily for 28 days, which contained 1/3 of the generally accepted daily requirement of protein. After four weeks of keeping animals on an experimental diet, acute toxic injury with acetaminophen was modelled. The toxin was administered at 1250 mg/kg of animal weight as a suspension in a 2% solution of starch gel once a day for 2 days. We found that acetaminophen toxic injury in the study group of rats leads to an increase in CYP450 and significant activation of microsomal monooxygenases in the liver with a simultaneous redistribution of hydroxylation and oxidation reactions in favor of oxidative N-dealkylation and N-oxidation, accompanied by excessive formation of NAPQI as opposed to non-toxic 3-OH-APAP. At the same time, acetaminophen toxic lesion of protein-deficient animals is accompanied by weakening of detoxification potential of the liver. We have shown a decrease in p-hydroxylase and N-demethylase activity against the background of direct N-oxidation of drug xenobiotic, as evidenced by the growth of N-oxygenase activity. The decrease in CYP450 content under these experimental. conditions is associated with an increase in the rate of its inactivation and transition to the inactive form, cytochrome P420. It should be noted that the administration of toxic doses of acetaminophen is a key factor in the intensification of superoxide generation, regardless of the amount of protein in the diet.
Keywords: Cytochrome P450; P-Hydroxylation; N-Demethylation; N-Oxidation; Superoxide Anion Radical; Acetaminophen; Alimentary Protein Deficiency; Liver; Rats of Reproductive Age